An integrated map of structural variation in 2,504 human genomes - Sudmant, Peter H.; Rausch, Tobias; Hsi-Yang Fritz, Markus; Stütz, Adrian M.; Meiers, Sascha; Schlattl, Andreas; Untergasser, Andreas; Zichner, Thomas; Korbel, Jan Oliver (Nature, 2015)
Structural variants are implicated in numerous diseases and make up the majority of varying nucleotides among human genomes. Here we describe an integrated set of eight structural variant classes comprising both balanced and unbalanced variants, which we constructed using short-read DNA sequencing data and statistically phased onto haplotype blocks in 26 human populations. Analysing this set, we identify numerous gene-intersecting structural variants exhibiting population stratification and describe naturally occurring homozygous gene knockouts that suggest the dispensability of a variety of human genes. We demonstrate that structural variants are enriched on haplotypes identified by genome-wide association studies and exhibit enrichment for expression quantitative trait loci. Additionally, we uncover appreciable levels of structural variant complexity at different scales, including genic loci subject to clusters of repeated rearrangement and complex structural variants with multiple breakpoints likely to have formed through individual mutational events. Our catalogue will enhance future studies into structural variant demography, functional impact and disease association.
Gesehen am 23.06.2020